The Creative Wealth of Nations How the Performing Arts Can Advance Development and Human Progress - Kabanda, Patrick (World Bank Policy Research Working Paper, 2014)
Cultural activities are increasingly noted as drivers of meaningful development. But they have yet to gain a prominent place in the architecture of development strategy. The performing arts, discussed here, exhibit direct effects on social progress and economic growth through trade in music, movies, and temporary work permits for artists, for example. Indirect contributions may also include environmental stewardship, tourism, nation branding, social inclusion, cultural democracy, and shifting cultural behaviors. These direct and indirect contributions are not well documented. As such, how is the creative or cultural sector a crucial part of the wealth of nations, and how could the World Bank Group better leverage the performing arts in its development strategy? This discussion provides a broad snapshot, from arts education, to social inclusion, to international trade in services. Key constraints include: the paucity of data and the difficulty of measuring cultural activities, the challenge of intellectual property, and the unclear benefits of cultural tourism. Part I sets the stage. Part II then provides policy options to foster the performing arts as a promising engine for development. Suggestions include: 1. expanding direct involvement in artistic projects, 2. increasing the use of performing arts to address social issues, 3. collecting data, 4. promoting intellectual property training programs, 5. supporting digital platforms in the developing world that advance indigenous music, and 6. funding studies on such areas as cultural tourism. Progress still needs to be made in the discussion of the diverse ways that the performing arts can contribute to meaningful development.
Keywords: Economic Theory & Research, Social Development & Poverty, Information Technology, Industrial Economics, Economic Growth, International Trade and Trade Rules